1991
DOI: 10.1002/bit.260370812
|View full text |Cite
|
Sign up to set email alerts
|

Affinity chromatography as a rapid and convenient method for purification of fungal laccases

Abstract: A rapid and convenient method for graduation, isolation, and purification of laccase from Trametes versicolor and Fomes fomentarius culture fluids was developed. For purification affinity chromatography on syringyl- and vanillyl-controlled porosity glass (CPG) columns was applied. The purified laccase of F. fomentarius was immobilized on porous glass. Some properties of the immobilized enzyme in comparison to the free one are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…31,32 Water was distilled and passed through Milli-Q purification system. Thermogravimetric analyses (TGA) were done using Universal V4.3A TA Instrument.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 Water was distilled and passed through Milli-Q purification system. Thermogravimetric analyses (TGA) were done using Universal V4.3A TA Instrument.…”
Section: Methodsmentioning
confidence: 99%
“…21 However, Khan and Overend12 showed that a constitutive polyphenoloxidase from the same fungus was able to transform, in the presence of oxygen, a range of diand tri-substituted benzene rings containing at least one hydroxy group. Some of the reaction products were formed by aromatic ring cleavage.…”
Section: Introductionmentioning
confidence: 98%
“…Taking into account protein concentration methods, salting out [10,12,14,[23][24][25] and dead-end ultrafiltration (UF) [10, 12-14, 17-21, 24] are used predominantly, whereas evaporation [16], acetone precipitation [13] and lyophilisation [12,20] are not common procedures. Chromatography (ion exchange [10][11][12][13][14][17][18][19][20][21][22][23][24][25], affinity [16,17,22,23] and hydrophobic interaction [15]) seems to be an obvious technique of laccase separation. In the next group of separation processes, aimed at removing undesired small molecules, there is dialysis [10,12,14,15,17,20,[23][24][25], gel filtration [11-13, 16, 18, 20, 22, 25] and diafiltration [14,19,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, each preparation method consists of three main steps: (1) cell debris removal, (2) concentration of culture broth and (3) removal of undesired low and high molecular weight compounds. Separation of the culture broth from cell debris can be done by passing fluid through a filter paper [10][11][12][13][14][15][16][17][18], glass fibre filters [19] and Miracloth [20,21], by microfiltration (MF) [18] or centrifugation [13,14,22,23]. Taking into account protein concentration methods, salting out [10,12,14,[23][24][25] and dead-end ultrafiltration (UF) [10, 12-14, 17-21, 24] are used predominantly, whereas evaporation [16], acetone precipitation [13] and lyophilisation [12,20] are not common procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation